Sistema nervoso central de Hypoptopomatinae e Neoplecostominae (Siluriformes: Loricariidae): implicações filogenéticas - Rosa, Alaina Cristine [UNESP] (2015)
Since the first phylogenetic hypotheses for Hypoptopomatinae and Neoplecostominae, many changes have occurred due to the increase of its known diversity, which had great impact on the latest phylogenetic proposals. Came to light also problems involving the composition of both subfamilies due to differences between morphological and molecular analysis. Thus, new sources of data are fundamental to a better understanding of the diversity of groups, and contribute to the elucidation of their evolutionary history. Therefore, this study aimed to evaluate the contribution of neuroanatomical characters in a phylogenetic analysis to Hypoptopomatinae and Neoplecostominae, in order to assess its composition, the phylogenetic relationships within the subfamilies, and of these groups with other subfamilies of Loricariidae. Were analyzed 55 terminal taxa including the Loricariidae subfamilies Delturinae, Hypoptopomatinae, Hypostominae, Loricariinae, Neoplecostominae, representatives of Callichthyidae, which also belongs to the superfamily Loricarioidea, and Pimelodidae. The specimens were dissected and had their brain removed for morphological analysis. Phylogenetic analysis was performed using heuristic search, using the TNT software, version 1.1. 60 characters treated as non-additive and with equal weights were used. The results support the monophyly of Loricariidae, and three of its subfamilies (Hypoptopomatinae, Loricariinae and Neoplecostominae). The analysis showed particularly good resolution at the level of subfamily, although the relationship between them presented fluctuations, which appears to be primarily related to Loricariinae taxa, which as a result is the most diverse group regarding to the central nervous system. Loricariinae was recovered as the most basal subfamily. The subfamily Neoplecostominae was found composed by Pareiorhaphis hystrix, Isbrueckerichthys and Neoplecostomus, this one recovere ...